2019
DOI: 10.5811/westjem.2019.7.41489
|View full text |Cite
|
Sign up to set email alerts
|

Undocumented Patients in the Emergency Department: Challenges and Opportunities

Abstract: In the United States, undocumented residents face unique barriers to healthcare access that render them disproportionately dependent on the emergency department (ED) for care. Consequently, ED providers are integral to the health of this vulnerable population. Yet special considerations, both clinical and social, generally fall outside the purview of the emergency medicine curriculum. This paper serves as a primer on caring for undocumented patients in the ED, includes a conceptual framework for immigration as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…We identified 24 relevant publications: 376 399 20 observational studies 376 395 ; one interventional study 399 ; and three commentary publications. 396 – 398 All observational publications investigated ED utilization in immigrant vs non-immigrant groups, with some specifically assessing Latino populations. Two publications (10%) studied the fear of ED utilization among Latino populations.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 24 relevant publications: 376 399 20 observational studies 376 395 ; one interventional study 399 ; and three commentary publications. 396 – 398 All observational publications investigated ED utilization in immigrant vs non-immigrant groups, with some specifically assessing Latino populations. Two publications (10%) studied the fear of ED utilization among Latino populations.…”
Section: Resultsmentioning
confidence: 99%
“…We found that patients utilizing Emergency Medicaid were nearly three times as likely to die as patients utilizing commercial insurance ( These observations are aligned with research showing poorer health outcomes among patients who delay receiving care, particularly immigrants. 41,42,43 These patients also may have presented with more severe COVID-19 illness owing to a lack of engagement with health care and concerns over presenting for care in light of federal rulings on public charge and immigration enforcement. We found that Chinese patients were most frequently new to NYC H+H (50.6%), which may reflect their known reluctance to and delay in seeking care, as described above.…”
Section: Covid-19 Outcomes Of Asian American Patientsmentioning
confidence: 99%
“…With estimates suggesting that as many as 68% of undocumented immigrants lack health insurance coverage and that only about 1 in 5 ULIs having access to health insurance via their employer, it is perhaps not surprising that the health services that are deemed as preventative and/or require established care are also those that ULIs reported having the most difficulties with [12,13,18]. On the other hand, it is equally not surpring that ULIs reported that they encountered the least number of difficulties with emergency medical services as these services are typically available to most to some degree regardless of insurance status or immigration legal status [12,38]. Furthermore, referencing the robust literature suggesting that Latino/a do not seek mental health services at the same rate as their Non-Hispanic White counterparts and that they are more likely to receive mental health support from informal routes, it is also somewhat expected that participants would report the least number of difficulties in accessing this type of care [39,40].…”
Section: Assessment Of Resultsmentioning
confidence: 99%